2018
DOI: 10.1186/s12889-018-5156-8
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and caries in four-to-six year old English children: a cross-sectional study

Abstract: BackgroundObesity and caries are common conditions in childhood and can have significant implications on children’s wellbeing. Evidence into their association remains conflicting. Furthermore, studies examining the ssociation between obesity and caries commonly focus on individual-level determinants. The present study aimed to examine the association between obesity and caries in young English children and to determine the impact of deprivation and area-level characteristics on the distribution of the two cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 36 publications
2
22
2
2
Order By: Relevance
“…For young children, the BMI seems to have more negative effects on oral health. This finding contradicts those of Paisi et al, who suggested that there could be no measurable relationship until later in life . However, even younger children were included in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…For young children, the BMI seems to have more negative effects on oral health. This finding contradicts those of Paisi et al, who suggested that there could be no measurable relationship until later in life . However, even younger children were included in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…However, because this leads to an underestimation of expected effects, the actual effects should be even more relevant. Nevertheless, the univariate analysis shows a correlation between excessive body weight and the occurrence of caries, a correlation that could also be shown in a recent study by Paisi et al, in which a positive association between weight status and obesity was shown …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Province is much higher than that in Japanese (31.1%) 9 and English children (31.7%). 10 Compared with more developed countries such as Japan and England, Zhejiang is slower in terms of oral health promotion and treatment, which falls behind its economic development, 13 analysis showed that the prevalence of ECC increased significantly with age. 13 We believe that this is mainly attributed to the cumulative effect of age throughout life.…”
Section: The Prevalence Of Ecc In Children Aged 3-5 Years In Zhejiangmentioning
confidence: 99%
“…Although caries and nutritional problems in childhood have a common risk factor [5] and studies have investigated the relationship between these events, the literature offers inconclusive and conflicting findings [6]. Some studies indicate a positive association between caries in the primary dentition and the body mass index [7,8], whereas others have found an inverse association [9,10] or no association at all [11]. Moreover, a nonlinear association has been reported in which both children with overweight or obesity and those who are thin or very thin have a higher prevalence rate of dental caries than children in the ideal weight range [12,13].…”
Section: Introductionmentioning
confidence: 99%